Goethite-modified biochar restricts the mobility and transfer of cadmium in soil-rice system. (March 2020) - Kashif Irshad, Muhammad; Chen, Chong; Noman, Ali; Ibrahim, Muhammad; Adeel, Muhammad; Shang, Jianying
Abstract: Cadmium (Cd) contamination of paddy soils has raised serious concerns for food safety and security. Remediation and management of Cd contaminated soil with biochar (BC) and modified biochar is a cost-effective method and has gained due attention in recent years. Goethite-modified biochar (GB) can combine the beneficial effects of BC and iron (Fe) for remediation of Cd contaminated soil. We probed the impact of different BC and GB amendments on Cd mobility and transfer in the soil-rice system. Both BC and GB effectively reduced Cd mobility and availability in the rhizosphere and improved the key growth attributes of rice. Although BC supply to rice plants enhanced their performance in contaminated soil but application of 1.5% GB to the soil resulted in prominent improvements in physiological and biochemical attributes of rice plants grown in Cd contaminated soil. Sequential extraction results depicted that BC and GB differentially enhanced the conversion of exchangeable Cd fractions to non-exchangeable Cd fractions thus restricted the Cd mobility and transfer in soil. Furthermore, supplementing the soil with 1.5% GB incremented the formation of iron plaque (Fe plaque) and boosted the Cd sequestration by Fe plaque. Increase in shoot and root biomass of rice plants after GB treatments positively correlates with incremented chlorophyll contents and gas exchange attributes. Additionally, the oxidative stress damage in rice plants was comparatively reduced under GB application. These findings demonstrate that amending the soil with 1.5% GB can be a potential remediation method to minimize Cd accumulation in paddy rice and thereby can protect human beings from Cd exposure. Graphical abstract: Image 1 Highlights: GB reduced Cd in rhizosphere pore water by enhanced pH and altered Cd fractions. Applied GB enhanced the capacity/ability of rice plants against Cd-induced oxidative damage. GB also enhanced the formation of Fe plaque and inhibited Cd accumulation in rice. GB can remediate Cd toxicity in soil and avert Cd accumulation in rice.